Assessing muscular strength in youth: Usefulness of standing long jump as a general index of muscular fitness - Castro-Pinero, J.; Ortega, F. B.; Artero, E. G.; Girela-Rejon, M. J.; Mora, J.; Sjöström, M.; Ruiz, J. R. (The Journal of Strength and Conditioning Research, 2010)
The purpose of the present study was to examine the association among different measures of lower body muscular strength in children, and the association between measures of lower- and upper-body muscular strength. The study population comprises 94 (45 girls) healthy Caucasian children aged 6-17 years. Children performed several lower body explosive muscular strength tests (i.e., standing long jump [SLJ], vertical jump, squat jump, and countermovement jump) and upper body muscular strength tests (i.e., throw basketball, push-ups, and isometric strength exercises). The association among the study tests was analyzed by multiple regression. The SLJ was strongly associated with other lower body muscular strength tests (R2 = 0.829-0.864), and with upper body muscular strength tests (R2 = 0.694-0.851). The SLJ test might be therefore considered a general index of muscular fitness in youth. The SLJ test is practical, time efficient, and low in cost and equipment requirements.